Prioritas Pemakaian Anggaran Pada Klinik Kesehatan Berbasis Metode Simple Additive Weighting - Karmila, Karmila; Setiawan, Aries; Prawitasari, Dian; Dian Andika , Arditya; Sjamsul Hidajat, Moch; Prasetya, Jaka; Hallang Lewa, Andi; Kusumaningrum, Lely (Jurnal Transformatika, 2025)
Improper financial management and the inability to properly manage each expense will lead to an imbalance in the clinic's income and expenses. If this continues, the clinic will eventually become unable to operate. Each type of clinic expense naturally has a different level of importance, influenced by various variables such as the nominal amount of the expense, the time limit for the expense, the user of the expense, the level of importance, and the intended use. The problem that occurs is that meeting the clinic's needs often fails to prioritize expenses and does not consider the level of importance of the expenditure. An appropriate priority scale is needed to regulate the level of expenditure that will impact the clinic's financial resilience so that it can facilitate the smooth operation of the clinic, with the aim of the clinic being able to grow or develop for the smooth provision of health services to the community. One method that can be applied to help prioritize the use of the clinic's budget is simple additive weighting. From the results of trials on several datasets, an accuracy rate of 90% was produced.